Systematic Literature Review on Students' Reading Habits in Indonesia in the Era of Technology - Wiranatha, Putu Andre; Santosa, Made Hery (Gagasan Pendidikan Indonesia, 2024)
This systematic literature review aimed to explore the impact of massive technology use on the reading habits of students in Indonesia, with a focus on the impact of digital media on their reading behavior. This review covers studies from 2019 to 2024, a period marked by the COVID-19 pandemic and the transition to digital learning environments. The findings show that reading habits among Indonesian students are generally low in various regions, including Sumatra, Java, Kalimantan, Sulawesi and Papua. The widespread use of smartphones and computers for entertainment purposes, such as gaming, social media, and video streaming, has significantly reduced the time spent reading traditional or academic material. Although technology offers extensive access to educational resources, the dominant use of technology for recreational activities hinders the development of strong reading habits. This research shows that students' reading habits in Indonesia tend to be low and are influenced by the use of technology, especially smartphones and computers, which are more often used for entertainment than reading. Awareness and self-control in using technology are the keys so that students can utilize technology to improve their reading habits, so that technology can become a useful tool rather than an obstacle in the learning process.